Penerapan Algoritma Analytical Hierarchy Process (AHP) Untuk Menentukan Pola Penindakan Lalu Lintas - Anagora, Roni; Damuri, Amat; Hendratna, Gempa; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The background of this research is to make intelligent actions that can be applied to crack downon the highway, with smart measures, the human side can be eliminated and all can be done withthe system, so it will eliminate the mistakes that can be made by humans. The method used byreading a lot of journals as a basis for research, with a lot of reading will deepen the research topicin search, reading can also add knowledge and can find new problems that can be raised in a study.By using the system, it will make it easier for the police to supervise and act on traffic violationson the highway, the lack of police personnel in DKI Jakarta is one of the problems that results inlack of supervision and action and can only conduct raids at any time, Application of AnalyticalHierarchy Process Algorithm (AHP) And Decision Tree by making a system will greatly help thepolice. In this study, the authors make a proposed action system that can be used to carry out trafficcontrol on the road by applying the Analytical Hierarchy Process (AHP) and Decision TreeAlgorithm, by making a system of personnel shortages problem can be solved and in the future the police only do direct action if the problem is already serious and requires police personnel at thescene.